SMART TOURISM – CITY TOURISM RADAR: A Tourism Monitoring Tool at the City of Lisbon - Lobao, Filipa; de Castro Neto, Miguel; Aparicio, M. (CAPSI 2019, 2019)
The increasing demand for Lisbon has led to an uncontrolled access to the city’s main attractions, which is reflected in the number of visitors that can be encountered at the city. Smart tourism destinations are gaining relevance in smart cities in everyday life, and technology is intricated more than ever in the cities and its citizens. In the present work it is proposed a conceptual model to a city tourism dashboard and its materialization using open data from the city’s public portal, produced by the Lisbon City Council and other partners. It is also suggested a method to the conception of this tool and the main indicators that must be included based on the actual state of the art. It concludes with a proposal of future developments to perform on the smart tourism destinations area.